2021
DOI: 10.1371/journal.pone.0255976
|View full text |Cite
|
Sign up to set email alerts
|

COVID19-associated cardiomyocyte dysfunction, arrhythmias and the effect of Canakinumab

Abstract: Background Cardiac injury associated with cytokine release frequently occurs in SARS-CoV-2 mediated coronavirus disease (COVID19) and mortality is particularly high in these patients. The mechanistic role of the COVID19 associated cytokine-storm for the concomitant cardiac dysfunction and associated arrhythmias is unclear. Moreover, the role of anti-inflammatory therapy to mitigate cardiac dysfunction remains elusive. Aims and methods We investigated the effects of COVID19-associated inflammatory response on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
(32 reference statements)
1
5
0
Order By: Relevance
“…Beat irregularity and frequency changes were also observed in hiPSC-CM monolayers. Similarly, depressed Ca 2+ transient amplitude and increased spontaneous Ca 2+ release events were previously reported in hiPSC-CMs and rat ventricular myocytes exposed to serum from COVID-19 infected patients (90), possibly implicating cytokines as mediators of rhythm disturbances that could translate to higher organ level cardiac arrhythmias. Further studies are needed to discern which cytokine-receptor combinations might be critical to the CCS remodeling underlying the electrophysiological phenotype in COVID-19.…”
Section: Dsrna Activation Of Innate Immune Responses In the Absence O...supporting
confidence: 65%
“…Beat irregularity and frequency changes were also observed in hiPSC-CM monolayers. Similarly, depressed Ca 2+ transient amplitude and increased spontaneous Ca 2+ release events were previously reported in hiPSC-CMs and rat ventricular myocytes exposed to serum from COVID-19 infected patients (90), possibly implicating cytokines as mediators of rhythm disturbances that could translate to higher organ level cardiac arrhythmias. Further studies are needed to discern which cytokine-receptor combinations might be critical to the CCS remodeling underlying the electrophysiological phenotype in COVID-19.…”
Section: Dsrna Activation Of Innate Immune Responses In the Absence O...supporting
confidence: 65%
“…These small, spontaneous calcium release events are well known to be an underlying cause of DADs and ventricular arrhythmias in patients with underlying genetic heart disease such as catecholaminergic polymorphic ventricular tachycardia for example [29,30], and are therefore the likely cause of the DADs observed by patch clamp in CoV-2 S-mEm-induced syncytia. Interestingly, Dimai et al recently observed similar spontaneous calcium release events in otherwise normal hiPSC-CMs that were incubated in serum extracted from SARS-CoV-2 positive patients who were hospitalized for severe acute respiratory distress [31].…”
Section: Plos Onementioning
confidence: 77%
“…While COVID-19 was the not the initial focus of our work, recent clinical studies highlighted correlations between elevated Activin A levels and disease severity in COVID-19 ( 10 , 11 ). In one preclinical study, hiPSC-CM treated with serum from patients with COVID-19 displayed marked arrhythmia ( 55 ). However, the arrhythmia was not abolished by adding the IL-1β inhibitor canakinumab to the culture.…”
Section: Discussionmentioning
confidence: 99%